2017
DOI: 10.1007/s11357-017-0003-x
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacologically induced impairment of neurovascular coupling responses alters gait coordination in mice

Abstract: There is correlative evidence that impaired cerebral blood flow (CBF) regulation, in addition to promoting cognitive impairment, is also associated with alterations in gait and development of falls in elderly people. CBF is adjusted to neuronal activity via neurovascular coupling (NVC) and this mechanism becomes progressively impaired with age. To establish a direct cause-andeffect relationship between impaired NVC and gait abnormalities, we induced neurovascular uncoupling pharmacologically in young C57BL/6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 101 publications
0
52
0
Order By: Relevance
“…Recent evidence has suggested that the accumulation of senescent astrocytes may drive neurodegenerative disorders (Di Malta et al 2012) and recent work shows that clearance of senescent glial cells may help with by preventing the accumulation of Tau aggregates and prevent cognitive decline in mouse models (Bussian et al 2018;Baker and Petersen 2018). Pre-clinical studies have shown that pharmacological impairment of astrocytic function recapitulates cognitive deficits that are observed in old age (Tarantini et al 2017a). It is also noteworthy that irradiation-induced accumulation of senescent cells is associated with neurovascular dysfunction in animal models (Ungvari et al 2017).…”
mentioning
confidence: 99%
“…Recent evidence has suggested that the accumulation of senescent astrocytes may drive neurodegenerative disorders (Di Malta et al 2012) and recent work shows that clearance of senescent glial cells may help with by preventing the accumulation of Tau aggregates and prevent cognitive decline in mouse models (Bussian et al 2018;Baker and Petersen 2018). Pre-clinical studies have shown that pharmacological impairment of astrocytic function recapitulates cognitive deficits that are observed in old age (Tarantini et al 2017a). It is also noteworthy that irradiation-induced accumulation of senescent cells is associated with neurovascular dysfunction in animal models (Ungvari et al 2017).…”
mentioning
confidence: 99%
“…Neurovascular coupling (functional hyperemia) is a critical homeostatic mechanism that ensures adequate adjustment of cerebral blood flow to increases in the oxygen and nutrient demands of activated neurons (Ungvari et al 2017a;Csiszar et al 2017;Tarantini et al 2017b;Tarantini et al 2017c). Several cardiovascular risk factors promote cognitive decline by impairing neurovascular coupling.…”
Section: Measurement Of Neurovascular Coupling Responsesmentioning
confidence: 99%
“…There is strong evidence that impairment of neurovascular coupling responses associates with cognitive decline (Tarantini et al 2015;Tarantini et al 2017c). Neurovascular coupling responses are sensitive to a wide range of cardiovascular risk factors (Tarantini et al 2019;Tarantini et al 2018a;Toth et al 2014Toth et al , 2015bTarantini et al 2017dTarantini et al , 2018bToth et al 2017;Tucsek et al 2014b), including changes in the hemodynamic environment (De Silva and Faraci 2012;Dunn and Nelson 2014;Faraco et al 2016;Kazama et al 2004).…”
Section: Jugular Vein Ligation Does Not Affect Neurovascular Couplingmentioning
confidence: 99%
“…Recent advances in the study of cellular and molecular processes underlying neurovascular coupling has allowed for developing novel therapeutic strategies to restore microvascular blood flow, rescue neurovascular responses, and thus improving cognition in older individuals (62,64). Endothelial dysfunction is pervasive during vascular aging, thus it is likely that interventional strategies that improve cerebral blood flow will exert beneficial effects on other vascular beds as well in older individuals (62,72).…”
Section: Advances In Cardiovascular Agingmentioning
confidence: 99%